The role of environmental career resources as a mediator on the influence of optimism and self-esteem on subjective career success of millennial employees - Halvireski, Arif; Salendu, Alice (International Journal of Research in Counseling and Education, 2022)
Currently, over 17.6% of employed individuals are millennials, and by 2030, this proportion will reach 70%. However, the millennial age has a propensity for employment in pursuit of more subjective career success. This study aimed to examine optimism and self-esteem's effect on millennial employees' subjective career success using environmental career resources as mediators. This is a quantitative study using 237 millennial employees as the sample size. The Subjective Career Success Inventory (SCSI), Psychological Capital Questionnaire (PCQ), Rosenberg Self-Esteem Scale, and Career Resources Questionnaire (CRQ) were used in this research. The Jamovi application uses mediation analysis for data processing. According to the findings of this study, there are direct or indirect effects on subjective career success. Positive, direct, and significant effects of optimism and self-esteem on the career success of millennial employees. However, environmental career resources only significant as a mediator in the effect of optimism on subjective career success. Optimistic employees will be more confident in their ability to make career decisions. They will be able to build higher-quality social relationships that will assist them in achieving career success. Positive self-esteem in employees will motivate them to select a more successful position.